Pengaruh Sistem Informasi Akuntansi dan Sistem Pengendalian Internal Terhadap Kinerja Karyawan (Studi pada Koperasi di Kecamatan Kedungkandang, Kota Malang) - Diah Ayu Khurriyah; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to determine the significant effect of accounting information systems and internal control system either simultaneously or partially on the employee’s performance in cooperatives in Kedungkandang district, Malang city. All employees who are still active in the Kedungkandang sub-district cooperative, the researchers set as the population. To take the sample, the researcher used the Yamane formula to determine the number of samples, so that 154 respondents were obtained. This research is classified as quantitative research and the data collection uses a survey method, namely by distributing questionnaires. Multiple linear regression analysis became the method of data analysis in this study, and the test used in this study were descriptive statistical test, instrument test, classical assumption test, and hypothetical tests. The result of the study prove that the accounting information system and internal control system both simultaneously and partially on the employee’s performance in cooperatives in Kedungkandang district, Malang city. Keywords: Accounting information system, internal control system, employee performance.